Risk of Malignant Cancers in Inflammatory Bowel Disease - Loo, Simone Y (J Crohns Colitis, 2019)
OBJECTIVES: To explore the trends and the predictors of incident malignant cancer among patients with inflammatory bowel disease [IBD]. METHODS: We identified a cohort of all patients with incident IBD in Quebec, Canada, from 1998 to 2015, using provincial administrative health-care databases [RAMQ and Med-Echo]. Annual incidence rates [IRs] of cancer were calculated using Poisson regression and were compared with those of the Quebec population using standardized incidence ratios [SIRs ]. Temporal trends in these rates were evaluated by fitting generalized linear models. Conditional logistic regression was used to estimate odds ratios [ORs] for predictors associated with cancer development. RESULTS: The cohort included 35 985 patients with IBD, of which 2275 developed cancers over a mean follow-up of 8 years (IR 785.6 per 100 000 persons per year; 95% confidence interval [CI] 754.0–818.5). The rate of colorectal cancer decreased significantly from 1998 to 2015 [p < 0.05 for linear trend], but the incidence remained higher than expected, compared with the Quebec population [SIR 1.39; 95% CI 1.19–1.60]. Rates of extraintestinal cancers increased non-significantly over time [p = 0.11 for linear trend]. In the IBD cohort, chronic kidney disease [OR 1.29; 95% CI 1.17–1.43], respiratory diseases [OR 1.07; 95% CI 1.02–1.12], and diabetes mellitus [OR 1.06; 95% CI 1.01–1.11] were associated with an increase in the incidence of cancer. CONCLUSIONS: The decreasing rates of colorectal cancer suggest improved management and care in IBD. Further studies are needed to explore the impact of comorbid conditions on the risk of cancer in IBD.